Barriers to early diagnosis of cervical cancer: a mixed-method study in Côte d'Ivoire, West Africa - Marie K. Plaisy; Simon P. Boni; Patrick A. Coffie; Aristophane Tanon; Adoubi Innocent; Apollinaire Horo; François Dabis; Anne Bekelynck; Antoine Jaquet; for the IeDEA West Africa Collaboration (BMC, 2023)
Abstract Background Cervical cancer, a major public health problem in many developing countries, is usually associated with a poor survival related to an advanced disease at diagnosis. In Côte d'Ivoire and other developing countries with high cervical cancer prevalence, little is known about factors associated with advanced cervical cancer stages in a context of limited access to screening services. Methods From May to July 2019, we conducted a cross-sectional study using a mixed, quantitative and qualitative method. Information on socio-demographic and history of the disease was extracted from a rapid case ascertainement study performed by the cancer registry of Côte d'Ivoire that enrolled all women diagnosed with cervical cancer between July 2018 and June 2019. In-depth semi-structured interviews were conducted among a subset of these women (12 women) and six healthcare providers to further capture barriers to early cervical cancer diagnosis. Factors associated with an advanced stage III, IV (according to FIGO classification) were estimated by a logistic regression model. Qualitative data were analyzed using a thematic analysis technique guided by the treatment pathway model and triangulated with quantitative data. Results In total, 95 women with cervical cancer [median age = 51 (IQR 42-59)] years, were included. Among them, 18.9% were living with HIV and only 9.5% were covered by a health insurance. The majority (71.5%) were diagnosed with advanced cervical cancer. Being HIV-uninfected (aOR = 5.4; [1.6-17.8], p = 0.006) and being uninsured (aOR = 13.1; [2.0-85.5], p = 0.007) were independently associated with advanced cervical cancer in multivariable analysis. Qualitative data raised additional factors potentially related to advanced cervical cancer stages at diagnosis, including the lack of patient information on cervical cancer by healthcare providers and inadequate national awareness and screening campaigns. Conclusion In a context of challenges in access to systematic cervical cancer screening in Côte d'Ivoire, access to health insurance or integrated healthcare program appear to be key determinants of early diagnosis of cervical cancer.